2021
DOI: 10.1007/s43440-021-00271-x
|View full text |Cite
|
Sign up to set email alerts
|

Formyl peptide receptor 2, as an important target for ligands triggering the inflammatory response regulation: a link to brain pathology

Abstract: Formyl peptide receptors (FPRs) belong to the family of seven-transmembrane G protein-coupled receptors. Among them, FPR2 is a low affinity receptor for N-formyl peptides and is considered the most promiscuous member of FPRs. FPR2 is able to recognize a broad variety of endogenous or exogenous ligands, ranging from lipid to proteins and peptides, including non-formylated peptides. Due to this property FPR2 has the ability to modulate both pro- and anti-inflammatory response, depending on the nature of the boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 129 publications
(166 reference statements)
0
29
0
Order By: Relevance
“…Several studies have demonstrated that LXA4 mediates responses related to RoI through the activation of N-formyl peptide receptors (FPRs) belonging to the G-protein coupled receptor family [22,32]. FPRs form higher-order structures (e.g., FPR1/FPR2 heterodimers, FPR2 homodimers, FPR1 homodimers), which lead to altering the downstream intracellular signaling pathways by allowing the co-localization of effector domains, enhancing intracellular activation, or creating new ligand specificity [35][36][37]. The beneficial role in the suppression of inflammation is primarily mediated through the FPR2 receptor [32,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that LXA4 mediates responses related to RoI through the activation of N-formyl peptide receptors (FPRs) belonging to the G-protein coupled receptor family [22,32]. FPRs form higher-order structures (e.g., FPR1/FPR2 heterodimers, FPR2 homodimers, FPR1 homodimers), which lead to altering the downstream intracellular signaling pathways by allowing the co-localization of effector domains, enhancing intracellular activation, or creating new ligand specificity [35][36][37]. The beneficial role in the suppression of inflammation is primarily mediated through the FPR2 receptor [32,38].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, LXA4 can directly bind to FPR2 with high affinity (Kd of 1.7 nM), but also to a variant of mouse mFpr-rs-1 [22,39]. The expression of FPR2 has been reported in the brainstem, spinal cord, thalamus/hypothalamus, cerebral neocortex, hippocampus, cerebellum, and striatum [33] in selected neurons [40] and also by microglia [34], in which FPR2 is rapidly upregulated following an inflammatory insult [35]. Moreover, the FPR2 is also expressed in many other cell types including neutrophils, eosinophils, monocytes, macrophages, T cells, synovial fibroblasts, and intestinal and airway epithelial cells [41], as well as neural stem cells [42].…”
Section: Introductionmentioning
confidence: 99%
“…FPRs form high-order structures (e.g., FPR1/FPR2 heterodimers, FPR2 homologous dimers, and FPR1 homologous dimers) that cause changes in downstream intracellular signaling pathways, allowing the colocalization of effector domain, enhancing intracellular activation, or creating new ligand specificity [ 49 , 50 ]. Some studies have shown evidence that the function of FPRs is associated with many diseases, such as inflammatory disorders, cancer, and infections [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has not yet been ascertained whether the increase in FPR2/ALX triggers inflammatory damage or acts as an endogenous compensatory outcome for the reduced SPMs in the pathological brain to perform neuroprotection. Tylek et al (2021) introduced the dual actions of FPR2/ALX on inflammatory response regulation in the brain and explained them by the concept of biased agonism. Interestingly, LXs did not show "dual-faced" effects on FPR2/ ALX and have been always acting as anti-inflammatory mediators.…”
Section: The Synthesis Of Lipoxinsmentioning
confidence: 99%